Food waste recovery pathways: Challenges and opportunities for an emerging bio-based circular economy. A systematic review and an assessment. (1st March 2021) - Santagata, R.; Ripa, M.; Genovese, A.; Ulgiati, S.
Abstract: The transition towards a Circular Economy in the agri-food supply chain will require appropriate support mechanisms. Globally, 1/3 of food is wasted, generating by-products which could be treated and processed. In a bioeconomy perspective, qualitatively and quantitatively assessing the availability of secondary raw materials and classifying the different conversion systems is crucial for the transition to happen. For this reason, a literature review of food waste conversion pathways, and related trade-offs and opportunities, has been carried out. Ecological performances of EU28 food waste treatment processes have been assessed through Life Cycle Assessment and Emergy Accounting methods, providing information from a donor and a consumer side perspectives for supporting policies. The added value of this work is the commixture of the analysis of food waste recovery and recycle pathways, their environmental assessment and the indication of opportunities and constraints. A conversion pathways database has been generated and classified. A major interest towards recovery of mixed food waste and biological type of conversion processes is highlighted. The main identified opportunities are the reduced environmental pressure and better management of resources, the avoided loss of economic value and the generation of work opportunities, as well as conditioning stakeholders' behaviors. On the other hand, it is highlighted that bad management of food waste can pose a threat on human health. The planning of these processes must carefully acknowledge local characteristics. Highlights: A review of Circular Economy food waste conversion pathways is provided. Nearly 200 conversion pathways are compared and critically evaluated. LCA and Emergy Accounting are applied to assess food waste treatment options. Opportunities and challenges linked to food waste recovery pathways are discussed.